Fact, fiction or Photoshop: Building awareness of visual manipulation through image editing software. Issue 2 (3rd April 2021) - Swerzenski, J. D.
Abstract: Among the most difficult aspects of building visual literacy is creating awareness of manipulation, a task made continuously harder by the prevalence of 'Photoshopped' or digitally altered photos through fake news or our everyday usage of photo editing apps. So how are educators to build awareness of visual literacy when manipulation has become ubiquitous? I argue that understanding the credibility of visual content must go beyond viewing the image as identifying whether a photo has or has not been manipulated. Instead, it requires a technical comprehension of the process by which images are created, allowing educators to discern between visual lies and everyday image editing. To this end, I position Photoshop as a teaching tool, one that offers educators and students a backstage view at the mechanisms of image alteration technology. In building a technical and rhetorical understanding of three key Photoshop tools—airbrush, layers, and filters—I outline a guide for using these tools grounded in critical considerations of how their use affects visual meaning. From this understanding, educators can move beyond blanket criticism of visual manipulation and into the ethical nuances of photo editing that distinguish meme from misinformation.